Overall Assay of Neuronal Signal Propagation Pattern With Long-Term Potentiation (LTP) in Hippocampal Slices From the CA1 Area With Fast Voltage-Sensitive Dye Imaging - Tominaga, Yoko; Taketoshi, Makiko; Tominaga, Takashi (Frontiers in Cellular Neuroscience, 2018)
Activity-dependent changes in the input-output (I-O) relationship of a neural circuit are central in the learning and memory function of the brain. To understand circuit-wide adjustments, optical imaging techniques to probe the membrane potential at every component of neurons, such as dendrites, axons, and somas, in the circuit are essential. We have been developing fast voltage-sensitive dye (VSD) imaging methods for quantitative measurements, especially for single-photon wide-field optical imaging. The long-term continuous measurements needed to evaluate circuit-wide modifications require stable and quantitative long-term recordings. Here, we show that VSD imaging (VSDI) can be used to record changes in circuit activity in association with theta-burst stimulation (TBS)-induced long-term potentiation (LTP) of synaptic strength in the CA1 area. Our optics, together with the fast imaging system, enabled us to measure neuronal signals from the entire CA1 area at a maximum frame speed of 0.1 ms/frame every 60 secs for over 12 hrs. We also introduced a method to evaluate circuit activity changes by mapping the variation in recordings from the CA1 area to coordinates defined by the morphology of CA1 pyramidal cells. The results clearly showed two types of spatial heterogeneity in LTP induction. The first heterogeneity is that LTP increased with distance from the stimulation site. The second heterogeneity is that LTP is higher in the stratum pyramidale-oriens region than in the stratum radiatum. We also showed that the pattern of the heterogeneity changed according to the induction protocol, such as induction by theta burst stimulation (TBS) or high-frequency stimulation (HFS). We further demonstrated that part of the heterogeneity depends on the I-O response of the circuit elements. The results show the usefulness of VSDI in probing the function of hippocampal circuits.